Organic and inorganic fertilizers on growth and yield of Vigna radiata L. sown after wheat crop in Nawalparasi West, Nepal - Bhattarai, Sagar (2024)
The purpose of this study is to know the effect of different organic and inorganic fertilizers on the growth and yield of mung beans cultivated after the harvest of wheat in the Nawalparasi district of Nepal. An experiment was carried out at Sarawal rural municipality, Nawalparasi West district, Lumbini Province during the summer season of 2023. In this experiment, five treatments were used. The treatments included: T1: Control, T2: NPK (0:20:20 kg.ha-1), T3: Recommended NPK dose (20:20:20 kg.ha-1), T4: Farm Yard Manure(FYM) (5 t.ha-1), and T5: Wheat residue (3 t.ha-1) incorporation. The experiment was laid out in a Randomized Complete Block Design to the above five treatments which were replicated four times with an area of each plot 2.4 m2. During this study period, the highest temperature recorded was 42.7 °C and the minimum temperature was 26 °C. Data on plant growth parameters like plant height, number of leaves, and yield parameters were measured. From the results, it was found that growth parameters like plant height at 15, 45, and 60 DAS and number of leaves at 60 DAS were significantly influenced by fertilizers treatment. Similarly, all the yield parameters like pods per plant, seeds per pod, 1000-grain weight, seed yield, and biological yield were significantly influenced by different fertilizers. All parameters showed better performance at NPK (20:20:20 kg.ha-1). Major growth parameters were highest at NPK (20:20:20 kg.ha-1) and lowest at control. Pods per plant, seeds per pod, 1000-grain weight (TGW), and harvest index were also higher in plots where the recommended dose of NPK fertilizer was applied. The maximum seed yield (0.71 t.ha-1) was found in NPK (20:20:20 kg.ha-1) than other treatments. Similarly, the harvest index of mung bean was the highest (25.39 %) in NPK (20:20:20 kg.ha-1) and the lowest in control (22.41 %). This concludes that the performance of major growth parameters and yield parameters were better under the recommended dose of NPK (20:20:20 kg.ha-1) fertilizer resulting in higher yield.